2010
DOI: 10.1177/0021998310381544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preparation on morphology-properties relationships in SAN/EPDM/PCC composites

Abstract: Mechanical and morphological properties of composites containing styrene—acrylonitrile (SAN) copolymer, ethylene— propylene—diene (EPDM) polymer, and different types of precipitated calcium carbonate (PCC) were investigated and their properties were analyzed in regard to PCC surface properties and the way of sample preparation (with or without use of a masterbatch (MB)). Contact angles of test liquids on PCC samples were measured in order to determine surface free energies of filler and to predict strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Since U1S2 has weak interactions with the polymers (predicted by theoretical calculation), this was expected. It is important to notice that, neither of the filler locations cannot guarantee neither good nor bad mechanical properties of polymer blend composites because they always depend on overall system morphology .…”
Section: Resultsmentioning
confidence: 99%
“…Since U1S2 has weak interactions with the polymers (predicted by theoretical calculation), this was expected. It is important to notice that, neither of the filler locations cannot guarantee neither good nor bad mechanical properties of polymer blend composites because they always depend on overall system morphology .…”
Section: Resultsmentioning
confidence: 99%
“…SSA is a function of porosity, pore size distribution, shape, size, and roughness. [162] In general, most mechanical properties of filed polymer will increase as the specific surface area increases. As such it improves the interfacial adhesion and compatibility with polymer matric that are chemically dissimilar.…”
Section: Specific Surface Areamentioning
confidence: 99%
“…The purpose of surface modification of calcium carbonate with stearate and silica with methacrylsilane was to increase their dispersion in HDPE polymer matrix and establish interaction with WF. 15 Addition of proper coupling agent and/or lubricant in order to increase phase adhesion has been demonstrated in many studies. [16][17][18][19][20] Wielage et al 17 showed that using a low-molecular weight coupling agent (lubricant) can dramatically increase the tensile strength of WPCs by better wetting of the WF and polymer matrix.…”
Section: Introductionmentioning
confidence: 99%